Systematic Literature Review: Isolation of Anthocyanin Compounds from Sweet Potato (Ipomoea batatas) - Subakir Salnus (Hayyan Journal, 2025)
Anthocyanins are natural pigments belonging to the flavonoid group, widely found in various plant parts, particularly fruits, flowers, and peels, where they are responsible for red, purple, and blue colors. These compounds possess extensive potential in the fields of food, health, cosmetics, and pharmaceuticals due to their bioactive properties, especially as antioxidants. However, anthocyanins exhibit low stability against environmental factors such as temperature, pH, light, oxidation, and processing conditions, which affects the effectiveness of their isolation and utilization in practical applications. Therefore, an appropriate modern technological approach and process optimization ranging from extraction and purification to product stabilization—are required. This Systematic Literature Review (SLR) aims to comprehensively analyze various isolation techniques for anthocyanins from sweet potatoes, including conventional and technology-assisted extraction methods, purification techniques, stability challenges, and opportunities for developing sustainable industrial methods. Literature searches were conducted on published scientific articles between 2016–2026 , initially yielding a total of 274 publications, from which 13 articles were selected according to the inclusion criteria. The majority of studies utilized the tubers as the source of anthocyanins. The review findings indicate that the optimization of extraction methods is proven to be crucial. Methods such as ASE, UAE, HPCD, and SCCO2 offer significantly higher yields compared to conventional extraction. This review is expected to serve as a scientific reference for the development of efficient, eco-friendly, and commercially valuable anthocyanin isolation technology.